Imprecision in the questions formulated by the chemistry teachers of the Kamina I subdivision and their impact on the performance of students in the science section - Pascal Mutombo; Crispin Muleba (IJRDO- Journal of Educational Research, 2024)
In this didactic study on the inaccuracies noted in the questions formulated bychemistry teachers, we sought to highlight these inaccuracies, identify theirsources, indicate their consequences on student performance and reformulatethese imprecise questions.The analysis of the five questions retained in this research led us to notethat:•The inaccuracies and their sources differ from each other, from one question toanother;•The embarrassment of students faced with the diversity of answers, thesubjective evaluation on the part of teachers as well as the failure of students arethe main consequences of these inaccuracies